ANALISIS PENGARUH MOTIVASI PERTUMBUHAN DAN ORGANIZATION-BASED SELF ESTEEM TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING - Yenti, Veny; Yuniawan, Ahyar (Diponegoro Journal of Management, 2018)
Growth motivation organization-based self esteem are related with needs satisfaction issues that was proposed as one of ERG Theory and self concept of oneself in organization therefore it held an important role in forming employeeâ€™s organizational commitment in their workplace. this research was designed in aiming the analyses and result implementation while studying the effect of growth motivation towards organizational commitment, the effect of obse towards organizational commitment. The effect of organizational commitment towards employee performances, the effect of growth motivation towards employee performances and obse towards employee performances.Present study used 95 employees of PT.PLN as the sample for the research while the population has 200 employees in total. Kind of technique that was used to do the sampling was quota sampling. Method of analyse in present study was multiple regression linear analysis and also path analysis method that has been proven as one of method that can be used to determine the causality connection among variables. Present study also run validity and reliability testing, classic assumption testing, hypothesis testing with t test , f test and r2test, sobel test was also usedÂ  to perform a more reliable result caused by mediation effect.Present study has several results in a form of statements which concludes that growth motivation and obse has a positive and significant effect towards organizational commitment, growth motivation and obse has a positive and significant effect towards employee performances, organizational commitment has a positive and significant effect towards employee performances, there is a mediation effect caused by organizational commitment as the intervening variable in relation betweem growth motivation and employee performances, last there is a mediation effect caused by organizational commitment as intervening variables in define the relation between obse and employee performances.